Spectroscopy of atomic and molecular defects in solid 4He using optical, microwave, radio frequency, magnetic and electric fields (Review Article) - Moroshkin, P.; Hofer, A.; Ulzega, S.; Weis, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
A little more than a decade ago our team extended the field of defect spectroscopy in cryocrystals to solid 4He matrices, in both their body-centered cubic (bcc) and hexagonally close-packed (hcp) configurations. In this review paper we survey our pioneering activities in the field and compare our results to those obtained in the related fields of doped superfluid helium and doped helium nanodroplets, domains developed in parallel to our own efforts. We present experimentaldetails of the sample preparation and the different spectroscopic techniques. Experimental results of purely optical spectroscopic studies in atoms, exciplexes, and dimers and their interpretation in terms of the so-called bubble model will be discussed. A large part of the paper is devoted to optically detected magnetic resonance, ODMR, processes in alkali atoms. The quantum nature of the helium matrix and the highly isotropic shape of the local trapping sites in the bcc phasemake solid helium crystals ideal matrices for high resolution spin physics experiments. We have investigated the matrix effects on both Zeeman and hyperfine magnetic resonance transitions and used ODMR to measure the forbidden electric tensor polarizability in the ground state of cesium. Several unexpected changes of the optical and spin properties during the bcc—hcp phase transition can be explained in terms of small bubble deformations.